2008
DOI: 10.1021/jp0776762
|View full text |Cite
|
Sign up to set email alerts
|

Accelerating Resolution-of-the-Identity Second-Order Møller−Plesset Quantum Chemistry Calculations with Graphical Processing Units

Abstract: graphics card. Furthermore, speedups of other matrix algebra based electronic structure calculations are anticipated as a result of using a similar approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
157
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 151 publications
(159 citation statements)
references
References 18 publications
2
157
0
Order By: Relevance
“…15 Previously we showed that step 4, the formation of the approximate MO integrals, was by far the most expensive operation for medium to large-sized systems, and requires the matrix multiplication…”
Section: Gpu Acceleration Of Ri-mp2mentioning
confidence: 99%
See 2 more Smart Citations
“…15 Previously we showed that step 4, the formation of the approximate MO integrals, was by far the most expensive operation for medium to large-sized systems, and requires the matrix multiplication…”
Section: Gpu Acceleration Of Ri-mp2mentioning
confidence: 99%
“…15 Concerning the batching over occupied orbitals, as discussed in section 4.2, only the step 4 matrices were batched. For taxol, the batch size was 7, as before.…”
Section: Ri-mp2 Acceleration Benchmarksmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Graphical processing units (GPUs), which are characterized as stream processors, 12 are especially suitable for parallel computing involving massive data and numerous groups have explored their use for electronic structure theory. [13][14][15][16][17][18][19][20][21][22][23][24] Implementation of gas phase ab initio molecular calculations [19][20][21] on GPUs led to greatly enhanced performance for large systems. [25][26] Here, we harness the advances 27 of stream processors to accelerate the computation of implicit solvent effects, effectively reducing the cost of PCM calculations.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these exciting developments in basic theory, fast numerical algorithms, and novel hardware utilization, [1][2][3][4][5] it is not yet possible to routinely simulate such large systems using readily available computer resources. However, emerging nano-scale simulation challenges involving, for example, large biomolecular aggregates or nanotechnology devices are increasing the demand for firstprinciples methods that can deliver this performance.…”
Section: Introductionmentioning
confidence: 99%